PENDIDIKAN AGAMA SEKOLAH MENENGAH PERTAMA: STUDI KASUS NEED-ASSESSMENT GPA DI KALIMANTAN TIMUR - Abdul M. Muin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2006)
However, religious education teachers' requirement is an important and strategic factor to be fulfilled. Based on the data, its requirement either on State Junior Secondary School or Private Junior High School in Balikpapan, East Kalimantan can be said that it already fulfilled the requirement based on the calculation ratio between the religious education teachers and the students. It means that every Junior Secondary School, state and private, already available the religious education teachers', so the students have been taught religious teaching as their beliefs and taught by the teacher who has the same religion with them. The problem is how the schools able to fulfill that requirement. In the State Junior Secondary Schools, it is not a big problem because the government supports it. But, the Private Junior High Schools face this as a serious problem. The problem of religious education teachers' requirement comes from internal and external of Junior Secondary School. Internally, it is about fund. Meanwhile, externally it is more founded on the government policy which has not yet sided on the Private Junior Secondary Schools.